ANALISIS RASIO PENERIMAAN DAN PENGELUARAN PEDAGANG PENGEPUL RUMPUT LAUT (Eucheuma Sp) DI DESA BINALAWAN KECAMATAN SEBATIK BARAT KABUPATEN NUNUKAN - Nova Liswan; Qoriah Saleha; Oon Darmansyah (2339-1324, 2024)
Nova Liswan, 2022. An Analysis of Revenue Cost Ratio among Seaweed (Eucheuma Sp) Collector Traders in Binalawan Village, West Sebatik, Nunukan District (Supervised by Qoriah Saleha and Oon Darmansyah).Nunukan District, including Sebatik Island, is extremely potential for seaweed growth as the stretch of coastline with the rocky and sandy seabed as well as protected and relatively calm water areas strongly support the seaweed cultivation business. Each business that is undertaken expends some costs to make the marketing activities result in revenue. This study aimed to calculate the Revenue Cost Ratio among seaweed collector traders and describe the marketing channel of seaweed cultivation in Binalawan village, West Sebatik sub- district, Nunukan district. This study used a census method (saturated) and a snowball sampling technique. The data analysis was done using the Revenue Cost Ratio as well as the marketing channel. The result of the analysis of the Revenue Cost Ratio or R/C was 1.45 and the marketing channel formed a two- level channel.